Agroinfiltration for transient gene expression and characterisation of fungal pathogen effectors in cool-season grain legume hosts - Debler, Johannes W. (Plant Cell Rep, 2021)
KEY MESSAGE: Modified pEAQ-HT-DEST1 vectors were used for agroinfiltration in legumes. We demonstrate protein expression and export in pea, lentil, and faba bean; however, the method for chickpea was not successful. ABSTRACT: Agroinfiltration is a valuable research method for investigating virulence and avirulence effector proteins from pathogens and pests, where heterologous effector proteins are transiently expressed in plant leaves and hypersensitive necrosis responses and other effector functions can be assessed. Nicotiana benthamiana is widely used for agroinfiltration and the characterisation of broad-spectrum effectors. The method has also been used in other plant species including field pea, but not yet developed for chickpea, lentil, or faba bean. Here, we have modified the pEAQ-HT-DEST1 vector for expression of 6 × histidine-tagged green-fluorescent protein (GFP) and the known necrosis-inducing broad-spectrum effector necrosis and ethylene-inducing peptide (Nep1)-like protein (NLP). Modified pEAQ-based vectors were adapted to encode signal peptide sequences for apoplast targeting of expressed proteins. We used confocal microscopy to assess the level of GFP expression in agroinfiltrated leaves. While at 3 days after infiltration in N. benthamiana, GFP was expressed at a relatively high level, expression in field pea and faba bean at the same time point was relatively low. In lentil, an expression level of GFP similar to field pea and faba bean at 3 days was only observed after 5 days. Chickpea leaf cells were transformed at low frequency and agroinfiltration was concluded to not be successful for chickpea. We concluded that the pEAQ vector is suitable for testing host-specific effectors in field pea, lentil, and faba bean, but low transformation efficiency limits the utility of the method for chickpea. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00299-021-02671-y.